Integrative-Interconnective Model: Implementation in Islamic Religious Education Curriculum Development in Muhammadiyah Schools - Ummu Afifah Nuriyatu Zahroh; Tasman Hamami; Samsul Bahri (CV. Ridwan Publisher, 2023)
Education in Indonesia has long been trapped in a dichotomy between religious knowledge and general science. As a result, it can lead to educational dualism at the practical level which in turn will result in a decline in educational outcomes. To unravel the split in knowledge between religious science and general science, a multi- and interdisciplinary paradigm is needed in the form of integrative-interconnective science. This paper aims to analyze the implementation of the development of Islamic Religious Education curriculum materials with an integrative-interconnective model in Muhammadiyah boarding schools. The type of research chosen in this paper is qualitative research with literature studies. The application of the integrative-interconnective model in the Islamic Religious Education curriculum needs to pay attention to three main principles, namely; hadarah al-nash, which serves as a cultural buffer for religious texts, hadarah al-'Ilm (science and technology), and hadarah al-falsafah (ethical-emancipatory culture). This gives the meaning that all learning materials must be sourced from the Al-Qur'an, therefore the Al-Qur'an must be the main reference in this matter. In addition, it must also be supported by scientific facts that have been proven empirically, so that its credibility can be recognized, and it needs to be supported by principles that originate from conscience or intuition. If these three principles can be implemented in learning materials, then it will be able to create comprehensive learning and understanding.